THE USE OF ISLAMIC EDUCATION VALUES FOR MULTI-RELIGIOUS STUDENTS TO ACHIEVE TOLERANCE ATTITUDES - Eriyanto Eriyanto; Arfandi Arfandi; St. Shofiyah; Mahendra Dhore (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
Junior High School 1 Songgon is an educational institution that incorporates three religions into its curriculum—Islam, Hinduism, and Christianity and excels in terms of knowledge without sacrificing its students' attitudes or character. This study aims to explore the impact of encouraging Islamic religious education values on the tolerant attitudes of multi-religious students. The goal is to foster both intellectual and emotional intelligence, as well as positive attitudes and character traits. This is qualitative research, including data collected through observation, interviews, and documentation. The author analyzed data by gathering, reducing, presenting, and drawing conclusions. This study found that instilling Islamic religious education ideals in multireligious pupils at Junior High School 1 Songgon leads to a tolerant mindset. There is no discrimination between Muslim and non-Muslim students. Everyone in the Junior High School 1 Songgon environment desires the same treatment and educational services from educators and each other, who are all unified and aid each other regardless of their socioeconomic situation. The researcher's findings show that Muslim and non-Muslim students interact and mingle without feeling inferior or embarrassed to socialize. Instilling Islamic religious education values can foster tolerance among students of different religions.